Metabolic dysfunction-associated fatty liver disease and metabolic-associated steatohepatitis: a review of pathogenesis and potential pharmacological targets - Samaneh Olapour; Hamid Yaghooti (Fiyz̤, 2022)
Background: Metabolic dysfunction-associated fatty liver disease (MAFLD) is one of the most common liver diseases that results from excess fat accumulation in the hepatocytes. The progression of steatosis to hepatocellular necrosis and inflammation leads to metabolic-associated steatohepatitis (MASH). Insulin resistance and obesity have significant roles in the disease process. Oxidative damage to hepatocytes and gut microflora dysbiosis may also contribute to the progression of fatty liver disease. There is currently no specific medication for MAFLD, and usually, lifestyle modifications are recommended. This study aimed to review the potential pharmacological targets for MAFLD. Materials and Methods: In this paper, we studied the primary pharmacological targets for MAFLD and MASH, focusing on current evidence from clinical trials registered on the WHO International Clinical Trials Registry Platform (ICTRP) and published articles in PubMed, Google Scholar, ISI Web of Science, and Scopus databases. Results: The peroxisome proliferator-activated receptors (PPARs), glucagon-like peptide-1 (GLP-1), farnesoid X receptor, statins, mediators of fibrosis and inflammation, weight loss agents, and probiotics were the primary targets in the treatment of fatty liver disease. Conclusion: The drugs decreasing body weight, such as orlistat and GLP-1 analogs, have beneficial effects in obese patients with fatty liver disease. Moreover, insulin-sensitizers and lipid-lowering agents like PPAR agonists, GLP-1 analogs, and statins are valuable in this condition.